The Effect Of Acid Treatment On The Characteristics Of Modernite Zeolite - Sumiati Side; Suriati Eka Putri; Diana Eka Pratiwi; Aulia Rahma; Abd. Rahman (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2023)
This work investigated the use of acid treatment on the characteristics of zeolite mineral. The effects of treating zeolite with various acid solutions hydrochloric acid (HCl) and sulfuric acid (H2SO4) were measured using x-ray fluorescence (XRF), x-ray diffraction (XRD), and scanning electron microscope (SEM). The results showed an increase in the percentage of SiO2 and Al2O3 after zeolite activation, and also a decrease in the amount of impurities. The crystalline phase of the zeolite was carried out using XRD analysis, indicating the type of zeolite used is modernite. The SiO2 phase in the sample is quartz, and the Al2O3 phase is corundum. The average crystal size decreased after activation, from 14.23 nm to 6.85 nm for HCl and 5.42 nm for H2SO4. Futhermore, the surface morphology of all zeolite samples has a form of irregular spherical surface, and the surface size of the particles after activation shows a smaller particle shape. The results of this study are expected to become recommendations for further research related to natural zeolite pretreatment as a catalyst support.